2018
DOI: 10.1021/acsami.8b09879
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical Self-Assembly of Multifunctional Hydroxyapatite with a Coral-like Nanostructure for Osteoporotic Bone Reconstruction

Abstract: Bone defects/fractures are common in older people suffering from osteoporosis. Traditional hydroxyapatite (HA) materials for osteoporotic bone repair face many challenges, including limited bone formation and aseptic loosening of orthopedic implants. In this study, a new multifunctional HA is synthesized by spontaneous assembly of alendronate (AL) and FeO onto HA nanocrystals for osteoporotic bone regeneration. The chemical coordination of AL and FeO with HA does not induce lattice deformation, resulting in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…These results were also confirmed by the mean optical density (MOD) studies in Figure S3 . As a result, it was inferred that the beneficial effects of calcium supplement in reversing osteoporosis were also partially attributed to the BMP-2-induced osteoblast differentiation 42 , which finally resulted in synergistic osteoblast promotion with Sim for better osteoporosis therapy. As expected, the calcium supplement (using ACC) or osteoblast promotion (using Sim) significantly reduced the TRAP activity than that in OVX group.…”
Section: Resultsmentioning
confidence: 99%
“…These results were also confirmed by the mean optical density (MOD) studies in Figure S3 . As a result, it was inferred that the beneficial effects of calcium supplement in reversing osteoporosis were also partially attributed to the BMP-2-induced osteoblast differentiation 42 , which finally resulted in synergistic osteoblast promotion with Sim for better osteoporosis therapy. As expected, the calcium supplement (using ACC) or osteoblast promotion (using Sim) significantly reduced the TRAP activity than that in OVX group.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Quan et al . [30] prepared a new multifunctional that HAP is synthesized by spontaneous assembly of alendronate and Fe 3 O 4 onto HAP nanocrystals, for osteoporotic bone regeneration, it can inhibit osteoclastic activity and promote osteoblast proliferation and differentiation. This indicated that Fe 3 O 4 alone or in combination with other materials was beneficial to enhance cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the presence of the paramagnetic nanoparticles in the hydroxyapatite scaffold induced the osteoblast growth and proliferation as a consequence of the modification of the osteoclast-derived exosomal cargo and of the reduction of the exosome uptake efficiency by osteoblasts. The positive effects induced by iron oxide superparamagnetic nanoparticles dispersed in the HA scaffolds both in vivo and in vitro experiments were even reported when the Fe 3 O 4 nanoparticles were co-dispersed in 3D HA matrix in the presence of alendronic acid (AA) [65], which is known to inhibit the osteoclast differentiation and to enhance the osteoblastic activity [66]. Further, the nanoparticles were capped by poly(ethylene glycol) functionalized with carboxyl groups in order to interact with calcium ion of HA.…”
Section: Mnps Enriched Scaffolds Without the Application Of An Externmentioning
confidence: 99%